Oil well: brief description - M. Yassin, Abu Azam; Ismail, Abdul Razak; Othman, Ariff; Hashim, Ayob; Kamis, Azmi; Hamid, M. Fauzi; Abdul Manan, Muhammad; Shahrudin, Shahrin; Hassan, Zulkafli (Penerbit UTM, 1988)
This book was translated from English to Malay. The early section of Chapter 1 describes the rig components. Other topics covered are drill string design, directional drilling, fracture gradient, casing design, etc.